Infection Mechanism of SARS-COV-2 and Its Implication on the Nervous System - Reza-Zaldívar, Edwin Estefan; Hernández-Sapiéns, Mercedes Azucena; Minjarez, Benito; Gómez-Pinedo, Ulises; Márquez-Aguirre, Ana Laura; Mateos-Díaz, Juan Carlos; Matias-Guiu, Jorge; Canales-Aguirre, Alejandro Arturo (Frontiers in Immunology, 2021)
In late December 2019, multiple atypical pneumonia cases resulted in severe acute respiratory syndrome caused by a pathogen identified as a novel coronavirus SARS-CoV-2. The most common coronavirus disease 2019 (COVID-19) symptoms are pneumonia, fever, dry cough, and fatigue. However, some neurological complications following SARS-CoV-2 infection include confusion, cerebrovascular diseases, ataxia, hypogeusia, hyposmia, neuralgia, and seizures. Indeed, a growing literature demonstrates that neurotropism is a common feature of coronaviruses; therefore, the infection mechanisms already described in other coronaviruses may also be applicable for SARS-CoV-2. Understanding the underlying pathogenetic mechanisms in the nervous system infection and the neurological involvement is essential to assess possible long-term neurological alteration of COVID-19. Here, we provide an overview of associated literature regarding possible routes of COVID-19 neuroinvasion, such as the trans-synapse-connected route in the olfactory pathway and peripheral nerve terminals and its neurological implications in the central nervous system.